Review of Evaporative Cooling Systems for Buildings in Hot and Dry Climates - Misrak Girma Haile; Roberto Garay-Martinez; Ana M. Macarulla (Buildings)
Evaporative cooling systems have gained increasing attention as an energy-efficient solution for climate control in hot and dry regions. This review aims to assess the effectiveness of the most recent advancements in evaporative cooling technologies for building applications in hot and dry climates. The review focuses on global literature, with an emphasis on building applications. The findings of this review indicate that evaporative cooling systems with hybrid configurations, particularly multi-stage systems, can achieve cooling efficiencies of up to 95%. These systems are highly energy-efficient, with energy consumption ranging from 0.3 to 1.2 kW/t, with hybrid and multi-stage designs showing the best performance. Direct and indirect evaporative cooling systems also perform well, with cooling effectiveness ranging from 60% to 85%. Their reliance on water, rather than harmful refrigerants, results in minimal environmental impact, making them an eco-friendly alternative to traditional cooling methods. The coefficient of performance (COP) for these systems is favorable, with hybrid and multi-stage designs reaching COP values as high as 35, indicating substantial cooling output relative to energy input. In addition, the performance of evaporative cooling systems is highly influenced by their design parameters and operating conditions. Advanced designs that incorporate multi-stage cooling and effective water management tend to provide enhanced cooling capacity and energy efficiency. Therefore, evaporative cooling systems are an excellent option for sustainable building practices, contributing significantly to energy savings and reduced environmental impact.